Myapps programme trains graduates to be technocrats - UMP, PNC
A total of 90 third-year undergraduates of Universiti Malaysia Pahang (UMP) underwent entrepreneurial training in ICT Technopreneur Incubator Programme (MyAPPS) organised by UMP Entrepreneurial Centre.